Bio-safety of Helicoverpa-resistant transgenic chickpea with Bacillus thuringiensis genes in the environment - SHARMA, H C; DHILLON, M K (The Indian Journal of Agricultural Sciences, 2018)
With the advent of recombinant DNA technology, it has become possible to clone and insert genes into the crop plants to confer resistance to insect pests. Genes conferring resistance to insect pests have been inserted into several crops, and efforts are underway to develop transgenic chickpea with resistance to pod borer, Helicoverpa armigera(Hubner) – which causes an estimated loss of over $500 million annually. However, concerns have been raised regarding the impact of genetically engineered plants on the non-target organisms, gene flow, and biosafety of the food derived from genetically engineered plants. There is no issue related to gene flow involving transgenic chickpea as most ofthe studies have indicated little or